2018
DOI: 10.3354/meps12448
|View full text |Cite
|
Sign up to set email alerts
|

Philopatry in loggerhead turtles Caretta caretta: beyond the gender paradigm

Abstract: Marine turtles have been traditionally considered model organisms to study sexbiased behaviour and dispersal. Although female philopatry has been identified in the loggerhead turtle, with adult females returning to specific locations to nest, studies on the philopatry and breeding migrations of males remain limited. In this study we analysed 152 hatchlings using 15 microsatellite markers. Each individual came from a different nest from samples taken at 8 nesting grounds in the Mediterranean. Our results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 92 publications
2
19
0
Order By: Relevance
“…Male sea turtles have uncertain philopatry and probably display greater flexibility in their choice of mating areas (FitzSimmons et al 1997). Similar patterns were found in previous studies using nDNA and are indicative of lack of male philopatry (FitzSimmons et al 1997; Bowen et al 2005; Carreras et al 2011; Vilaça et al 2013; Clusa et al 2018). Thus, the apparently discrepant results for mtDNA and multilocus data could be further explained by male-mediated gene flow between rookeries.…”
Section: Discussionsupporting
confidence: 89%
“…Male sea turtles have uncertain philopatry and probably display greater flexibility in their choice of mating areas (FitzSimmons et al 1997). Similar patterns were found in previous studies using nDNA and are indicative of lack of male philopatry (FitzSimmons et al 1997; Bowen et al 2005; Carreras et al 2011; Vilaça et al 2013; Clusa et al 2018). Thus, the apparently discrepant results for mtDNA and multilocus data could be further explained by male-mediated gene flow between rookeries.…”
Section: Discussionsupporting
confidence: 89%
“…This is a highly valuable characteristic of 2b‐RAD methodology, since not all studies can easily access high quality samples. For instance, marine turtle genetic studies usually rely on sampling of stranded individuals (Clusa et al, 2016) or dead embryos found at nests after excavation (Clusa et al, 2018), due to the complexity of their behaviours and the paucity of individuals. In such cases, a genomic protocol capable of providing optimal results with degraded samples is invaluable.…”
Section: Discussionmentioning
confidence: 99%
“…Juveniles of D. puntazzo were collected in Blanes ( N = 12) and Xabia ( N = 12) (Spain) during recruitment using hand nets (Figure 1). Samples of C. caretta were taken from bycaught juveniles at the foraging ground off Valencia (Spain) ( N = 9; Figure 1) and from dead hatchlings at the nesting ground west of Sirte (Lybia) ( N = 14; Clusa et al, 2018). We also added a sample collected from a live female turtle nesting in Pulpí (Spain) as positive control (Carreras et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the natural recovery of isolated populations on the verge of extinction may be difficult, as little migration would be expected from other populations to increase the number of mating adults. This philopatric behaviour, in both females and males (Clusa et al, ), is the basis for a rapid colonization of new potential nesting areas after the first arrival of marine turtles (Carreras et al, ).…”
Section: Introductionmentioning
confidence: 99%